E. Fuglei & A. Tarroux. Arctic fox dispersal from Svalbard to Canada: one female’s long run across sea ice - Fuglei, Eva; Tarroux, Arnaud (Polar research, 2019)
This Erratum relates to the following article: E. Fuglei & A. Tarroux. Arctic fox dispersal from Svalbard to Canada: one female’s long run across sea ice. Polar Research 2019, 38, 3512, http://dx.doi.org/10.33265/polar.v38.3512 The following error requires a correction in the above referenced article (page 4, left column, second paragraph): “When travelling on sea ice, her average movement rate was 34.0 km/day (95% confidence interval = 16.5–51.5) (Fig. 3), suggesting that sea ice was used predominantly as a platform for dispersal, rather than as a foraging habitat.” This has now been changed to read as follows: “Her average movement rate was higher by 34.0 km/day (95% CI: 16.5–51.5) when travelling on sea ice than when travelling on land (Fig. 3), suggesting that sea ice was used predominantly as a platform for dispersal, rather than as a foraging habitat.” This correction does not change the interpretation of the results. The editorial office regrets the error.